Nrf2 Overexpression Decreases Vincristine Chemotherapy Sensitivity Through the PI3K-AKT Pathway in Adult B-Cell Acute Lymphoblastic Leukemia - Wang, Li; Liu, Xin; Kang, Qian; Pan, Chengyun; Zhang, Tianzhuo; Feng, Cheng; Chen, Lu; Wei, Sixi; Wang, Jishi (Frontiers in Oncology, 2022)
Uncontrolled proliferation is an important cancer cell biomarker, which plays a critical role in carcinogenesis, progression and development of resistance to chemotherapy. An improved understanding of novel genes modulating cancer cell proliferation and mechanism will help develop new therapeutic strategies. Apoptosis is directly associated with the nuclear factor erythroid 2-related factor 2 (Nrf2), a transcription factor. However, its clinical significance and function in B-cell acute lymphoblastic leukemia (B-ALL) are not yet established. Our results showed that Nrf2 levels can sufficiently modulate the sensitivity of B-ALL cells to vincristine (VCR) by regulating an apoptotic protein, i.e., the Bcl-2 agonist of cell death (BAD). Chemotherapeutic agents used for the treatment of B-ALL induced Nrf2 overactivation and PI3K-AKT pathway activation in the cells, independent of the resistance to chemotherapy; thus, a potential resistance loop during treatment for B-ALL with a drug combination is established. Therefore, Nrf2 may be a potential target for developing a novel combined treatment for B-ALL.